DEFENSE MECHANISM IN CHIMAMANDA NGOZI ADICHIE’S AMERICANAH - Nanang Purwo, Ishaq; Andayani, Ambar (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
Defense mechanism is a psychological occurrence in human mind to reduce excessive stress. The study analyses defense mechanism and the exposition of it in the characters of C.N. Adichie’s Americanah. The study is conducted to understand the process of defense mechanism through the related topics. This study uses descriptive qualitative research design to analyze the characters and explain the topics. The study uses psychoanalytical criticism approach which then combined with psychoanalysis and defense mechanism theory to analyze and understand defense mechanism. The researcher uses psychoanalysis and defense mechanism theory to analyze defense mechanism used and the process of it. The exposition of defense mechanism is then made according to the analysis. The study indicates the use of 5 defense mechanism in Ifemelu, which are Repression, Denial, Projection, Displacement, and Sublimation. It also indicates 2 defense mechanism Obinze has used, Displacement and Reaction Formation. This study also indicates that narrative are used to expose defense mechanism.